A product of logarithms

Algebra Level 2

Simplify and find the value of the following expression:

log 2 ( 3 ) log 3 ( 4 ) log 4 ( 5 ) log 5 ( 6 ) log 6 ( 7 ) log 1023 ( 1024 ) \log_{2}(3)\cdot\log_{3}(4)\cdot\log_{4}(5)\cdot\log_{5}(6)\cdot\log_{6}(7) \dots \log_{1023}(1024)


The answer is 10.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

P = log 2 3 × log 3 4 × log 4 5 × log 1023 1024 Using log b a = log a log b = log 3 log 2 × log 4 log 3 × log 5 log 4 × × log 1024 log 1023 = log 1024 log 2 = log 2 10 log 2 = 10 log 2 log 2 = 10 \begin{aligned} P & = \log_2 3 \times \log_3 4 \times \log_4 5 \times \cdots \log_{1023} 1024 & \small \color{#3D99F6} \text{Using }\log_b a = \frac {\log a}{\log b} \\ & = \frac {\cancel{\log 3}}{\log 2} \times \frac {\cancel{\log 4}}{\cancel{\log 3}} \times \frac {\cancel{\log 5}}{\cancel{\log 4}} \times \cdots \times \frac {\log 1024}{\cancel{\log 1023}} \\ & = \frac {\log 1024}{\log 2} = \frac {\log 2^{10}}{\log 2} = \frac {10\cancel{\log 2}}{\cancel{\log 2}} = \boxed{10} \end{aligned}

Kb E
Jan 2, 2018

Since log y ( x ) = log a ( x ) log a ( y ) \log_y(x) = \frac{\log_a(x)}{\log_a(y)} , this is equal to

log 2 ( 3 ) log 2 ( 2 ) log 2 ( 4 ) log 2 ( 3 ) log 2 ( 1024 ) log 2 ( 1023 ) = log 2 ( 1024 ) log 2 ( 2 ) = 10 \frac{\log_2(3)}{\log_2(2)}\cdot\frac{\log_2(4)}{\log_2(3)}\cdot\cdot\cdot \frac{\log_2(1024)}{\log_2(1023)} = \frac{\log_2(1024)}{\log_2(2)} = 10

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...